Identification of novel compound heterozygous variants in the PEX10 gene in a Han-Chinese family with PEX10-related peroxisome biogenesis disorders - Xiangjun Huang; Xinyue Deng; Xiong Deng; Hongbo Xu; Hao Deng; Lamei Yuan (PLoS ONE, 2025)
The peroxisome biogenesis disorders (PBDs) are a group of rare inherited autosomal recessive diseases characterized by motor and cognitive neurological dysfunction, hypotonia, seizures, feeding difficulties, retinopathy, sensorineural hearing loss, hepatic and renal abnormalities, and chondrodysplasia punctata of long bones, and the clinical expression is variable. Exome sequencing and Sanger sequencing were used to identify the genetic defect for PBDs in a two-generation non-consanguineous Han-Chinese pedigree. Compound heterozygous variants, a novel splicing variant c.113-2A>G and a reported substitution c.890T>C (p.Leu297Pro), in the peroxisomal biogenesis factor 10 gene (PEX10) were detected. The splicing variant c.113-2A>G led to a canonical splice acceptor site inactivation, exon 2 skipping, and in-frame deletions (p.Ala39_Gly65del). The three patients had similar phenotypes of milder PBDs, which were further genetically determined as PBD6B. The findings extend the PEX10 variant spectrum and may provide new insights into PBDs causation and diagnosis, with implications for genetic counseling and clinical management.